Clinical and imaging diagnosis of pediatric testicular microlithiasis: a physician’s dilemma - Habachi, Ghada; Kerkeni, Yosra; Riadh, Jouini (Frontiers in Pediatrics, 2025)
Testicular microlithiasis (TM) is a relatively rare and incompletely understood condition, particularly in the pediatric population. Its clinical significance and optimal diagnostic and therapeutic management remain subjects of ongoing debate. In order to clarify current practices and guide clinical decision-making, we conducted a literature review of recent studies published using the search terms testicular microlithiasis, testicular calculi, testicular neoplasm, and children. The primary objective of this review was to propose a standardized diagnostic management algorithm based on the available evidence. The nature of testicular microlithiasis remains a subject of ongoing debate. In the absence of definitive evidence, continued follow-up appears to be the safest approach to minimize the risk of delayed diagnosis in the event of malignant transformation or tumor development. Routine scrotal examination should be encouraged and properly taught, particularly to adolescents and their caregivers. Ultrasonographic (US) surveillance, while not mandatory, should be considered when accessible, especially in individuals with additional risk factors.